Guidelines for victim-sensitive victim-offender mediation:Restorative justice through dialogue - (:unkn) unknown (My University, 2016)
This monograph presents specific criteria and recommendations to enhance the overallquality of victim-offender mediation programs and promote far more victim-sensitive practicesin the field. The material presented is grounded in a yearlong assessment of the mostcurrent practices in the field, based on a nationwide survey. The material focuses on thepractice of victim-offender mediation and dialogue regarding property crimes and minorassaults, the kinds of offenses typically addressed through mediation. A small but growingnumber of victims of severe violence are requesting to meet with their offenders. This is,however, an intensive and lengthy process that requires advanced training for the mediator.Fully addressing the multitude of issues related to working with severely violent victimizationssuch as sexual assault, attempted homicide, or murder is beyond the scope of thismonograph.